Nilai-Nilai Pendidikan Islam dalam Tradisi Methik Pari di Desa Sidomulyo Perspektif Psikologi - Fuadi, Anwar; Krisnawati, Nova; Nurlaili, Lili; Novianto, Erik; Nugraha, Agus Bambang (Global Education Journal, 2023)
Javanese culture is one of the local cultures in the archipelago which is very rich and has a big influence in Indonesia. Javanese culture developed on the island of Java which is in the central part of Indonesia and has a strong influence in the surrounding areas. The purpose of this study is to explore the values of Islamic education contained in the methik pari tradition in Sidomulyo Village from a psychological perspective. This research method uses qualitative methods with an ethnographic approach. The results of the study state that the moral values of Methik pari in Sidomulyo Village from a psychological perspective contain Islamic educational values, perhaps referring to the fact that morals are an important aspect of Islam, and moral values in Islam are in line with Islamic educational values. So it can be concluded that the Methik pari tradition in Sidomulyo Village from a psychological perspective has Islamic educational values which are very important in the formation of good character and personality and can help individuals develop a better and healthier psychological side, so they can achieve a better life balance.